Memorial de formação acadêmico-profissional: da infância humilde ao ingresso na vida acadêmica e docente - BARBOSA, Jonas Borges (2023)
This memorial was produced to serve as a requirement for obtaining the degree in Pedagogy from the Federal University of Pará - Altamira university campus, it aims to rescue memories that are part of my personal, academic and professional trajectory, comparing them with the paradigms that are part of the debate on teaching. In this sense, here will be exposed ideas that debate these issues, both in the sense of the formation of the human personality as a whole and of the professional personality from the various inquiries that involve the formation of the teacher, bringing elements that corroborate this point of view, confronting experiences people with theory to reach an understanding of how these two strands come together and how important they are in the process that involves teacher training. This work is structured as follows: first we have the introduction that brings an autobiography, as well as a part of my life story, bringing elements of my family history that I judged relevant to the meaning of the text, I talk a little about the trajectory of my father and my mother and how this trajectory impacted my life, then comes the theoretical chapter that seeks to expose the theory that corroborates this work, making a comparison of what is being treated in the text with the ideas that deal with this subject in the academic world, seeking to demonstrate how memory is present in the formation of the individual and how it can be incorporated into the history of the professional in formation. After that, I return once more to my personal experience, I report on my formative process, from early childhood education to entering university, also talking about my professional experiences in the area of education, unraveling my formative trajectory and my work as a teacher, seeking to give greater meaning to what is being treated in this memorial. Finally, I make my considerations on the work presented here, seeking to emphasize how my distinct and diverse experiences and learning came together to form who I am, both as a social and professional being.